Cyber Threats Early Detection Countermesures and Benefits - Ambusaidi, Husam Hassan; Kumar, Dr Prakash (IJRDO -Journal of Computer Science Engineering, 2017)
In the recent years, the cyber-attacks have evolved and become more complex. Thecyber-attacks have moved from random attacks to targeted and high sophisticated attacks. Ona daily basis, companies and organizations are targeted by different and sophisticated cyberattacks. Many of these companies and organizations are unconscious that they are targeted bycyber threats and their networks are already compromised. Furthermore, vast majority ofcompanies and organizations are vulnerable to various cyber threats. Hence, to detect the cyberthreats and compromised networks at early stage the organizations need better mechanism forcyber threat detection. Several cyber security vendors have introduced advanced technologiesto allow early detection of the cyber threats. This research will discuss the importance of earlydetection for cyber threats. Furthermore, the research study the current emerged cyber threatswith relation to early detection. Further outcome, this paper research will identify the benefitsof proactive security protection.